Efeito da prometazina, fluoxetina e carbonilcianeto m-clorofenil-hidrazona (CCCP) como inibidores de bombas de efluxo em isolados clínicos de Pseudomonas aeruginosa multirresistentes - Pereira, Vinícius Carvalho (2023)
Multi-drug resistant (MDR) Pseudomonas aeruginosa represents a major health problem worldwide. The active efflux of antimicrobials represents an important pathway associated with this MDR phenotype. In addition, efflux pumps in this bacterial species also act in other aspects of bacterial physiology, such as in biofilm maintenance. Thus, the search for efflux pump inhibitors (EPIs) presents itself as an important alternative in the management of bacterial resistance and virulence. This research aimed to evaluate the action of promethazine (PMZ), fluoxetine (FLU) and carbonylcyanide m-chlorophenylhydrazone (CCCP) as EPIs in P. aeruginosa. The Minimum Inhibitory Concentrations (MICs) and the effect of EPIs on the metabolism and biomass of bacterial biofilms were determined. Accumulation assays with ethidium bromide (EtBr) were performed to prove the action of PMZ, FLU and CCCP as EPIs. Associations of PMZ, FLU and CCCP with classical antimicrobials (ciprofloxacin, gentamicin and meropenem) on planktonic cells and in biofilm were also performed. The study EPIs showed antibacterial and antibiofilm effects against the study strains with MICs ranging from 195.3 to 781.2 μg/mL for PMZ, 78.1 to 312.5 μg/mL for FLU and 256 to 2048 μM for CCCP and Minimum Eliminating Biofilm Concentrations (MBECs) ranging from 781, 2 to 6250 μg/mL for PMZ, 312.5 to 1250 μg/mL for FLU and 1024 to 4096 μM for CCCP, although FLU did not significantly reduce the biomass of these biofilms. Subinitory concentrations of PMZ, FLU and CCCP (MIC/2 and MIC/4) significantly increased the fluorescence of bacterial cells, indicating their action in inhibiting efflux pumps. Significant reductions in the metabolic activity of biofilms were observed after the association with the antimicrobials, especially for meropenem. The data from this study allow us to prove the action of PMZ, FLU and CCCP as EPIs in P. aeruginosa, and demonstrate the relevance of efflux pumps in antimicrobial resistance.